Blood Metabolic Profile in Barki Ewes during Transition Period - EL-SAYED, A.; EL-ASHKER, M.; IBRAHIM, Η.; SHOIEB, S.; IBRAHIM, F.; YOUSSEF, M.; EL-KHODERY, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
This technical research article investigated the changes in the hemato-biochemical profile in Barki ewes during the transition period. A total of 15 healthy pregnant Barki ewes (age, 4.9 ± 0.7 years old; weight, 38.5 ± 4.9 Kg) were randomly selected for the current study. Blood samples were collected from the selected ewes via jugular vein puncture during the transition period at five different time points; 4 and 2 weeks prior the estimated date of delivery (EDD), at the parturition time, then at 2 and 4 weeks post-partum. Red blood cells (RBCs) count and packed cell volume (PCV) were significantly (P<0.05) decreased 2 weeks before the EDD and at the parturition time. Mean corpuscular volume (MCV) was significantly (P<0.05) decreased 4 weeks post-partum. The neutrophil count and neutrophil/lymphocyte ratio were significantly (P < 0.05) increased 2 weeks post-partum. The level of β-hydroxy butyric acid (BHBA) and concentration of non-esterified fatty acid (NEFA) in the serum were significantly (P<0.05) increased 2 weeks before EDD, at the parturition time, and 2 weeks post-partum. Both cholesterol and triglyceride levels increased significantly (P<0.05) 2 weeks before EDD and at the parturition time. Leptin level was significantly (P<0.05) decreased at 2 weeks and 4 weeks post-partum. Glucose level increased significantly (P<0.05) at the parturition time then decreased significantly (P<0.05) at 2 weeks post-partum, after which it increased again 4 weeks post-partum. Total protein level was significantly (P<0.05) increased 2 weeks post-partum. The level of both calcium and inorganic phosphorus was significantly (P<0.05) decreased at the parturition time and 2 weeks post-partum. The results revealed that Barki ewes showed profound physiological alterations during the transition period which are not necessarily indicative of a disease, but reflect physiological variations. Therefore, metabolic profile test was needed to determine the nutritional status of Barki ewes, and to take the possible preventive measures that increase ewes’ productivity and predict health disorders.